The Impact of Destructive Online Behaviors on Social Stability: Contemporary Threats and Theoretical Approaches - Karimov Ulugbek Dilmurodjonovich (Peerian Journals Publishing, 2025)
This article analyzes the impact of increasingly prevalent destructive behaviors on the internet on social stability using a comprehensive approach. Against the backdrop of the rapid expansion of the information space, issues such as anonymity, fake news, cyberbullying, darknet activity, and other negative phenomena are shown to seriously disrupt the psychological, moral, and political balance of society. The study identifies the types, scale, and prevention mechanisms of such threats using systematic, comparative, documentary, and content analysis methods.
Keywords: Destructive behaviors; internet; security; social stability